2010
DOI: 10.1177/0003319710373094
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Nitric Oxide Synthase and Angiotensinogen Gene Polymorphism in Coronary Artery Diseases in Egypt

Abstract: Genetic factors contribute to the pathogenesis of coronary artery disease (CAD). We studied 100 patients with CAD and 50 healthy individuals to assess the association of endothelial nitric oxide (eNOS) polymorphism (Glu298Asp) and angiotensinogen polymorphisms (M235T) and CAD in an Egyptian population. Serum nitric oxide (NO) and angiotensin I levels were also measured. The frequency of Glu298Asp and M235T polymorphisms were higher in the CAD group compared with controls. The mean level of NO was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
(38 reference statements)
3
16
1
Order By: Relevance
“…41 Other independent studies have also reported that the AGT TT genotype was significantly elevated in Egyptian CAD patients compared to controls. 42, 43 In Tunisians, rs699 (M235T), and rs4762 (T174M) were also associated with CAD. 44 The Glu298Asp polymorphism in exon 7 of the nitric oxide synthase 3 ( eNOS ) gene was more frequently observed in Egyptians with CAD than controls.…”
Section: Genetics Of Cvd In Africamentioning
confidence: 95%
See 1 more Smart Citation
“…41 Other independent studies have also reported that the AGT TT genotype was significantly elevated in Egyptian CAD patients compared to controls. 42, 43 In Tunisians, rs699 (M235T), and rs4762 (T174M) were also associated with CAD. 44 The Glu298Asp polymorphism in exon 7 of the nitric oxide synthase 3 ( eNOS ) gene was more frequently observed in Egyptians with CAD than controls.…”
Section: Genetics Of Cvd In Africamentioning
confidence: 95%
“…44 The Glu298Asp polymorphism in exon 7 of the nitric oxide synthase 3 ( eNOS ) gene was more frequently observed in Egyptians with CAD than controls. 43 …”
Section: Genetics Of Cvd In Africamentioning
confidence: 99%
“…A total of 18 studies were conducted in the Asian population (7,16,20,21,23,25,26,(33)(34)(35)(36)(37)41,42,45,48,51,52) and 21 in the non-Asian population (17-19,22,24,27-32,38-40, 43,44,46,47,49-50). In terms of the source of the controls, 15 were from hosptial-based (HB) studies (16,17,20,24,25,28,30,34,35,37,41,43,45,47,51) and 24 were from population-based (PB) studies (7,18,19,(21)(22)(23)26,27,29,(31)(32)(33)36,(38)(39)…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Three comparisons (Motawi et al ,10 Atay e t al 19 and Sakar et al 21) were identified as the main contributors to the heterogeneity by using Galbraith plot. The MD value and 95% CI (MD −0.13 μmol/L, 95% CI −0.22 to −0.04 μmol/L, p heterogeneity =0.89, p MD <0.001) did not change substantially after excluding these outlier comparisons (table 2).…”
Section: Resultsmentioning
confidence: 99%